A Mixed-Methods Assessment of Health Care Providers' Knowledge, Attitudes, and Practices Around Fertility Awareness-Based Methods in Title X Clinics in the United States - Shelby Webb; An-Lin Cheng; Rebecca Simmons; Rachel Peragallo Urrutia; Victoria Jennings; Jacki Witt (Mary Ann Liebert, 2020)
Objective: To understand how Title X providers currently engage with fertility awareness-based methods (FABMs) for pregnancy prevention in Title X clinics across the United States. Materials and Methods: We developed a survey to assess knowledge of fertility for purposes of pregnancy prevention, attitudes toward FABMs use for pregnancy prevention, and practices when patients request FABMs for pregnancy prevention. Results: In total, 329 participants who met all inclusion criteria completed the survey. Respondents were generally highly knowledgeable on fertility, felt neutrally toward FABMs or thought they were a nonviable option for most women, and were likely to respond to patient requests for FABMs for pregnancy prevention by providing information. Qualitative responses included several barriers to provision of FABMs for pregnancy prevention and few successes to provision. Conclusions: Fertility knowledge and discussion of specific methods increased with the number of methods included in the clinic's written materials or with the number of different FABMs someone at that clinic had been trained on. Significant clinician or administrative barriers may exist to offering FABMs to patients. Incorporating up-to-date information on a range of FABMs?rather than treating them as one method?into contraceptive counseling represents an opportunity to increase the contraceptive offering for clients who want them, leading to increased patient satisfaction and successful family planning outcomes.